GEOMETRIC STRUCTURE ANALYSIS OF MBAH BUYUT KI TUAN TOMB GATE AS A CONTEXTUAL LEARNING RESOURCE FOR DECOMPOSITION OF THREE-DIMENSIONAL SHAPES IN ELEMENTARY SCHOOL STUDENTS - Margareta Sinta Wibawati; Wiryanto Wiryanto; Endah Budi Rahaju (FKIP Universitas Muhammadiyah Tangerang, 2026)
This research aims to analyze the potential of the geometric structure of the Mbah Buyut Ki Tuan Tomb gate in Karanglo Village as a contextual learning resource for three-dimensional shapes material, specifically decomposition skills and critical thinking enhancement in elementary school students. The study is motivated by the underutilization of local wisdom as an ethnopedagogical basis in mathematics learning, despite local traditions and cultural artifacts possessing strong visual-spatial values. The research employs a descriptive qualitative approach through direct observation, visual documentation, and interviews with local informants. Data were analyzed using reduction, categorization, and conclusion-drawing techniques. Results indicate that the tomb gate contains clearly identifiable three-dimensional shape elements recognizable to students, such as rectangular prisms in pillars and foundations, and cubes in upper ornamental sections. The gate structure can be decomposed into combinations of rectangular prisms and cubes, which can then be reconstructed as composite three-dimensional shapes. The analysis also reveals that utilizing this cultural object has potential to enhance the connection between mathematical concepts and real contexts, strengthen spatial visualization abilities, and promote critical thinking skills. Beyond mathematical values, relevant ethnopedagogical values were discovered, including respect for ancestors, mutual cooperation, and local cultural identity. The research concludes that the Mbah Buyut Ki Tuan Tomb gate is suitable as an ethnopedagogy-based contextual learning resource and can be integrated into digital media development, including Scratch, to enrich students' learning experiences. These findings provide a preliminary basis for developing locally culture-based mathematics learning media that is pedagogically valid and socially meaningful.